1995
DOI: 10.1159/000126869
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Correlates of the Aging Brain in Humans

Abstract: Physiological brain aging is characterized by important biochemical and structural changes and by the unbalance among the different neurotransmitters and neuromodulators. The study of the circadian organization of neuroendocrine functions may be considered a clinically reliable tool to investigate the changes of the CNS and particularly of the limbic-hypothalamic system occurring in aged people. The circadian rhythms of plasma melatonin, ACTH and cortisol and of oral temperature were studied in 16 clinically h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 19 publications
5
29
0
Order By: Relevance
“…1), allowed us to detect a high percentage of`non-responders' (serum cortisol levels above 5 mg/dl the morning following DXM (66), in healthy old subjects (about 30%) and in old demented patients (50%). Indeed, the mean cortisol values recorded after DXM were significantly higher in elderly subjects and especially in demented patients than in young controls; moreover, patients with senile dementia also exhibited a delay of the cortisol response to DXM (67).…”
Section: Cortisol Secretion and Agingmentioning
confidence: 93%
“…1), allowed us to detect a high percentage of`non-responders' (serum cortisol levels above 5 mg/dl the morning following DXM (66), in healthy old subjects (about 30%) and in old demented patients (50%). Indeed, the mean cortisol values recorded after DXM were significantly higher in elderly subjects and especially in demented patients than in young controls; moreover, patients with senile dementia also exhibited a delay of the cortisol response to DXM (67).…”
Section: Cortisol Secretion and Agingmentioning
confidence: 93%
“…Many studies have found an age-associated increase in HPA activity (Van Cauter et al, 1996), resulting in elevated cortisol levels (Lupien et al, 1994;Ferrari et al, 1995;Deuschle et al, 1997) and attenuation, or a flattening, of cortisol diurnal rhythm (van Coevorden et al, 1991) suggesting age-dependent HPA axis dysregulation. Additionally, it has long been speculated that chronic elevations of stress-related hormones such as cortisol can weaken multiple physiological systems of older adults resulting in impaired cardiovascular and immune function, as well as contributing to dementia, and mood and anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%
“…1996). Lowered melatonin levels are also associated with ageing (Iguchi et al 1982;Touitou et al 1984;Sack et al 1986; as potential subjects if they met the following criteria: mean sleep onset latency (SOL) < 30 min, WASO < 30 min, final Waldhauser et al 1988;Sharma et al 1989;van Coevorden et al 1991Ferrari et al 1995Hajak et al 1996). Ageing is wake-up time (FWUT) > 06.00 h, TST > 7.5 h and SE > 85%.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies report peak melatonin Attenburrow, M. E. J., Dowling, B. A., Sharpley, A. L. and Cowen, concentration is reduced in the aged (Iguchi et al 1982; Touitou P. J. Case-study of evening melatonin concentration in primary et al 1984;van Coevorden et al 1991Ferrari et al 1995insomnia. Br.…”
mentioning
confidence: 99%